Cross-Presentation: How to Get there – or How to Get the ER - Kreer, Christoph; Rauen, Judith; Zehner, Matthias; Burgdorf, Sven (Frontiers in Immunology, 2012)
Antigen cross-presentation enables dendritic cells to present extracellular antigens on MHC I molecules, a process that plays an important role in the induction of immune responses against viruses and tumors and in the induction of peripheral tolerance. In order to allow intracellular processing for cross-presentation, internalized antigens are targeted by distinct endocytic receptors towards specific endosomal compartments, where they are protected from rapid lysosomal degradation. From these compartments, antigens are processed for loading onto MHC I molecules. Such processing generally includes antigen transport into the cytoplasm, a process that is regulated by members of the ER-associated degradation (ERAD) machinery. After proteasomal degradation in the cytoplasm, antigen-derived peptides have been shown to be re-imported into the same endosomal compartment by endosomal TAP, another ER protein, which is recruited towards the endosomes after DC maturation. In our review, we highlight the recent advances on the molecular mechanisms of cross-presentation. We focus on the necessity of such antigen storage compartments and point out important parallels to MHC I-restricted presentation of endogenous antigens. We discuss the composition of such endosomes and the targeting of extracellular antigens into this compartment by specific endocytic receptors. Finally, we highlight recent advances on the recruitment of the cross-presentation machinery, like the members of the MHC I loading complex and the ERAD machinery, from the ER towards these storage compartments, a process that can be induced by antigen encounter or by activation of the dendritic cell after contact with endotoxins.